Bacteriological profiles and drug susceptibility of Streptococcus isolated from conjunctival sac of healthy children - Ruili Ke; Min Zhang; Qin Zhou; Yunfei Yang; Ruifen Shen; Huipin Huang; Xiangrong Zhang (BMC, 2020)
Abstract Background To investigate bacterial flora and antibiotics susceptibility of Streptococcus pneumoniae isolated from the conjunctival sac of heathy children. Methods Bacteria were isolated from the secretions of conjunctival sac of healthy children between 2015 and 2018. Antimicrobial susceptibility of isolated S. pneumoniae strains were determined using microbroth dilution method. Results The sac secretions were collected from a total of 6440 children. 1409 samples presented bacterial growth, accounting for 21.8% of the samples. Among the 22 bacterial species isolated, 528 samples presented Gram-positive Staphylococcus spp. growth, accounting for 37.4% of the isolates, followed by Corynebacterium spp., counting for 30% of the isolates and Streptococcus pneumoniae, counting for 21.4% of the isolates. Antibiotics susceptibility tests showed that the majority of S. pneumoniae isolates were sensitive to most antibiotics tested. However, 72.8 and 81.2% of the isolates were resistant to erythromycin and tetracycline, respectively, and over 10% of them were resistant to gentamicin, tobramycin and rifampicin. Conclusions The bacterial flora of healthy children is mainly consisted of Gram-positive bacteria belonging to Corynebacterium spp. and Streptococcus spp.; most of S. pneumoniae isolates were sensitive to antibiotics except erythromycin and tetracycline.